Reproductive health and multiparity: social representations and access to reproductive planning. - Lacerda Rodrigues, Alessandra; Ferreira Rodrigues, Eduarda Moniky; das Neves Figueiroa, Maria; Neto de Menezes, Maria Lúcia (Revista Enfermagem Digital Cuidado e Promoção da Saúde, 2023)
Objective: To analyze the social representations of multiparity and access to reproductive planning for multiparous women through the single health system. Method: This was a qualitative study, with a descriptive-exploratory approach, carried out with 7 multiparous women at a prenatal and reproductive planning clinic at the Amaury de Medeiros Integrated University Health Center. Data was collected using the focus group technique. Bardin’s content analysis was used to analyze the data. Results: The main challenge faced by women in terms of reproductive planning was the difficulty in accessing contraceptive methods. In addition, the loss of women’s autonomy was identified as the main consequence of multiparity. Self-responsibility for contraception also stands out, with unintended pregnancy being reported in their speeches as a lack of care on their part. Final considerations: The importance of considering social, cultural and economic factors in the reproductive planning program to meet the specific needs of multiparous women was noted.